150k views
2 votes
CAN SOMEONE SHOW ME HOW TO DO THIS PLEASE????????????????

CAN SOMEONE SHOW ME HOW TO DO THIS PLEASE????????????????-example-1
User Masterov
by
4.9k points

1 Answer

5 votes
For (h+g)(x) you just add the two functions:

(h+g)(x) = 4x + 2x^2

For (h•g)(x) you multiply them:

(h•g)(x) = 4x • 2x^2 = 8x^3

For (h-g)(x) you subtract them:

(h-g)(x) = 4x - 2x^2


For (h-g)(-2) you sub -2 into the equation we just created:

(h-g)(-2) = 4(-2) - 2(-2)^2
(h-g)(-2) = -8 - 2(4)
(h-g)(-2) = -8 - 8
(h-g)(-2) = -16
User ThurstonLevi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.